Annexin A5 levels or circulating microparticles: what we see depends mainly on what we look for. (22nd December 2015) - Patil, R.; Ghosh, K.; Shetty, S.
Abstract : Click here to view the article Letter to the Editor by C. Reutelingsperger et al.